Taboo Words in TikTok Comments: A Forensic Linguistic Study of Language Use on Social Media - Fitri, Nurul; Istiqamah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The research was conducted to understand the types and contexts of taboo words used in TikTok comment sections, as well as to examine their linguistic and legal implications based on forensic linguistic studies. This research used a qualitative descriptive approach to analyze data containing taboo words. The research data was obtained from the comment sections of the TikTok application containing taboo words. The data collection technique began with listening, noting, and documenting in the form of screenshots of comments. The data was then analyzed by identifying, classifying the types of taboo words, and relating them to the provisions of the Electronic Information and Transaction Law (ITE Law). The results showed that 14 data items were found to be taboo words. There were seven types of taboo words: 2 data points for cursing, 1 data point for obscene words, 1 data point for indecency, 2 data points for sexual harassment, 3 data points for vulgar language, and 5 data points for name-calling and insults, while no data points were found for blasphemy. The most dominant type of taboo word is name-calling and insults. The use of these taboo words has the potential to violate norms of decency, language ethics, and legal provisions in the ITE Law.